Cylinder steam injection (CSI) for internal combustion (IC) engine waste heat recovery (WHR) and its application on natural gas (NG) engine. (1st January 2021) - Liu, Qi; Xie, Mingke; Fu, Jianqin; Liu, Jingping; Deng, Banglin
Abstract: In this study, the approach of CSI for IC engine WHR was discussed based on a heavy-duty NG engine. The thermodynamic processes of IC engine cycle coupling with CSI cycle were investigated under three typical speeds of full load based on the calibrated model, and then the effects of steam injection parameters on engine performance especially thermal efficiency were studied. Results show that, the improvement of engine thermal efficiency is determined by both steam injection parameters and engine operating conditions. The earlier steam injection timing, higher steam temperature and larger steam amount are beneficial for improving the WHR efficiency. Although the higher steam temperature leads to lower steam amount generated by waste heat, the maximum improvement of engine thermal efficiency still appears at the highest steam temperature. Compared with original engine, the thermal efficiency of this NG engine can be improved by at least 6% points through steam injection, and the maximum improvement comes up to 6.6% points at 2000 rpm. Accordingly, the engine indicated power is increased by 38.6 kW at the expense of 0.29 kW pumping power. All these demonstrate that this WHR approach has great energy-saving potential for IC engine. Highlights: The effect of steam injection on the thermodynamic process of engine was discussed. The effective region of steam injection temperature was found. Steam injection has little effect on engine heat transfer and gas exchange processes. The maximum thermal efficiency of this combined cycle comes up to 53.1%. The maximum improvement of engine thermal efficiency comes up to 6.6% points.